Commuters Modal Choice: A Case Study of Savar Pourashava - Rahman, Md Lutfur; Islam, Md Monowarul; Al Mamun, Mohammad (Journal of Bangladesh Institute of Planners, 2012)
Commuter’s modal choice is a complex phenomenon in urban transportation. It is a key determinant of modern transport planning. Commuters always want to get a hold on any mode at any point of time to meet their travel demand and the selection of mode depends on various factors associated with the commuting. In Savar Pourashava, modal choice by commuters varies with commuter’s socio-economic background and demographic characteristics. It also varies with the services that are provided by the various modes operating in the study area. The land use characteristics also affect the travel behavior pattern of commuters in the study area. The attitude and preference of commuters towards modes are also varied from each other. For achieving efficient and reliable transportation system in terms of modal choice of the commuters in the study area, it is essential to identity various factors affecting the travel pattern of the commuters. This research has attempted to identity these factors in modal choice and investigated over the mode that has been preferred by individual commuters and the reasons for selection of the mode. Beside this, the research has explored the relationship between land use characteristics and travel behavior pattern of the commuters. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9569 Journal of Bangladesh Institute of PlannersVol. 2, December 2009, pp. 78-97